Economies of Scope in European Railways: An Efficiency Analysis - Heike Wetzel; Christian Growitsch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
In the course of railway reforms in the end of the last century, national European governments, as well the EU Commission, decided to open markets and to separate railway networks from train operations. Vertically integrated railway companies - companies owning a network and providing transport services - argue that such a separation of infrastructure and operations would diminish the advantages of vertical integration and would therefore not be suitable to raise economic welfare. In this paper, we conduct a pan-European analysis to investigate the performance of European railways with a particular focus on economies of vertical integration. We test the hypothesis that integrated railways realise economies of joint production and, thus, produce railway services on a higher level of efficiency. To determine whether joint or separate production is more efficient we apply a Data Envelopment Analysis super-efficiency bootstrapping model which relates the efficiency for integrated production to a virtual reference set consisting of the separated production technology. Our findings are that in a majority of European Railway companies exist economies of scope. – – Im Zuge der Reformen der europäischen Eisenbahnindustrie entschieden die nationalen Regierungen Europas sowie die EU Kommission, die Eisenbahnmärkte zu liberalisieren und die Schieneninfrastruktur vom Fahrbetrieb organisatorisch zu trennen. Vertikal integrierte Eisenbahnunternehmen - Unternehmen, die sowohl das Schienennetz als auch den Transportbetrieb unterhalten - äußern die Befürchtung, daß eine solche Separierung Vorteile der vertikalen Integration (sogenannte Verbundvorteile) vermindern würde und somit nicht geeignet sei, die gesamtgesellschaftliche Wohlfahrt zu erhöhen. In diesem Aufsatz untersuchen wir mittels einer pan-europäischen Analyse die Produktivität europäischer Eisenbahnunternehmen und berücksichtigen dabei insbesondere etwaige Verbundvorteile indem wir überprüfen, ob integrierte Eisenbahnunternehmen eine höhere technische Effizienz aufweisen als vertikal separierte Unternehmen. Dazu berechnen wir ein Data Envelopment Analysis super-efficiency bootstrapping Modell, das die Effizienz der integrierten Produktionstechnologie im Verhältnis zu einer Referenzgruppe virtueller, aus den separierten Unternehmen konstruierter Beobachtungseinheiten berechnet. Unsere Forschungsergebnisse weisen auf existierende Verbundvorteile für die Mehrzahl der europäischen Eisenbahnunternehmen hin.
urn:nbn:de:gbv:3:2-636
Keywords: L43; L22; L92; 330; Efficiency; Vertical Integration; Railway Industry